FORMULASI SEDIAAN LILIN EKSTRAK MINYAK ATSIRI BUNGA SEDAP MALAM (Polianthes tuberosa ) SEBAGAI AROMATERAPI - anggara, Elysa; Harahap, Nina Irmayanti (Jurnal Penelitian Farmasi Dan Herbal, 2025)
Stress is a common phenomenon that significantly impacts physical and mental health. One natural method widely developed to promote relaxation is aromatherapy. This study aimed to formulate tuberose (Polianthes tuberosa) essential oil into aromatherapy candles and evaluate their physical characteristics. Essential oil extraction was carried out using steam distillation, then formulated into candles using paraffin and stearic acid as the base ingredients. Four formulas with varying essential oil concentrations were selected: F1 (0 mL), F2 (5 mL), F3 (10 mL), and F4 (15 mL). Evaluation included organoleptic tests (color, aroma, and shape), homogeneity, melting point, and physical stability. The results showed that the candle with the addition of 15 mL of essential oil (F4) had the best physical characteristics: even color, a smooth surface, no cracks, easy lighting, and a strong, distinctive, calming aroma. Based on the evaluation results, tuberose essential oil was successfully formulated into a stable aromatherapy candle with the potential to provide a relaxing effect.